Predictability in orbital reconstruction: A human cadaver study. Part I: Endoscopic-assisted orbital reconstruction. Issue 10 (December 2015) - Dubois, Leander; Jansen, Jesper; Schreurs, Ruud; Saeed, Perooz; Beenen, Ludo; Maal, Thomas J.J.; Gooris, Peter J.J.; Becking, Alfred G.
Abstract: In the treatment of orbital defects, surgeon errors may lead to incorrect positioning of orbital implants and, consequently, poor clinical outcomes. Endoscopy can provide additional visualization of the orbit through the transantral approach. We aimed to evaluate whether endoscopic guidance during orbital reconstruction facilitates optimal implant placement and can serve as a convenient alternative for navigation and intra-operative imaging. Ten human cadaveric heads were subjected to thin-slice computed tomography (CT). Complex orbital fractures (Class III/IV) were created in all eligible orbits ( n  = 19), which were then reconstructed using the conventional transconjunctival approach with or without endoscopic guidance. The ideal implant location was digitally determined using pre-operative CT images, and the accuracy of implant placement was evaluated by comparing the planned implant location with the postoperative location. There were no statistically significant differences ( p  > 0.05) in the degree of implant dislocation (translation and rotation) between the transconjunctival orbital reconstruction and the endoscopic-assisted orbital reconstruction groups. Endoscopic-assisted orbital reconstruction may facilitate the visualization of orbital defects and is particularly useful for training purposes; however, it offers no additional benefits in terms of accurate implant positioning during the anatomical reconstruction of complex orbital defects.